In vitro comparison of Enterococcus Faecalis survival in dentinal tubules following root canal therapy with AH plus, endoseal MTA, and cold ceramic sealers - Fatemeh Mokhtari; Jalil Modaresi; Ali Hasanzade Salmasi; Nima Khamisi; Hengameh Zandi; Katayoun Lesani (BMC Oral Health)
Abstract Background Enterococcus faecalis (E. faecalis) is the most common microorganism responsible for post-endodontic infections, which can penetrate deep into dentinal tubules. This study aimed to compare the survival of E. faecalis in dentinal tubules following root canal therapy with AH Plus (AHP), Endoseal MTA (ESM), and cold ceramic (CC) sealers. Methods In this in vitro experimental study, 80 single-canal human teeth were decoronated at the cementoenamel junction. The root canals were cleaned and shaped, and auto-clave sterilized after smear layer removal. The roots were then inoculated with E. faecalis, and incubated for 3 weeks. The teeth were randomly assigned to four groups (n = 20) for root canal obturation with AHP, ESM, and CC sealers and 2% gutta-percha with the cold lateral compaction technique. The fourth group served as the control group. After 30 days, dentin chips were collected from the canals, and cultured on blood agar. The colony count was reported and analyzed by the Kruskal-Wallis test (alpha = 0.05). Results The mean colony count was 23.73 ± 13.84 in the AHP, 34.78 ± 18.75 in the ESM, and 28.47 ± 13.73 in the CC group after 30 days. The difference in this regard was not significant among the three experimental groups (P = 0.102). Conclusions Within the limitations of this in vitro study, the results indicated comparable antibacterial activity of AHP, ESM, and CC sealers against E. faecalis in infected dentinal tubules after 30 days.